1999
DOI: 10.1111/j.1469-7793.1999.0687u.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of homologous S4 mutations in human skeletal muscle sodium channels on deactivation gating from open and inactivated states

Abstract: The outermost charged amino acid of S4 segments in the α subunit of human skeletal muscle sodium channels was mutated to cysteine in domains I (R219C), II (R669C), III (K1126C), and IV (R1448C). Double mutations in DIS4 and DIVS4 (R219C/R1448C), DIIS4 and DIVS4 (R669C/R1448C), and DIIIS4 and DIVS4 (K1126C/R1448C) were introduced in other constructs. Macropatch recordings of mutant and wild‐type (hSkM1‐wt) skeletal muscle sodium channels expressed in Xenopus oocytes were used to measure deactivation kinetics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 35 publications
(68 reference statements)
5
35
0
Order By: Relevance
“…A charge-neutralizing arginine-to-cysteine substitution at the same position in hSkM1 (R669C) caused only a modest depolarizing shift of the G-V relationship of 5-7 mV (Mitrovic et al, 1998;Groome et al, 1999), similar to the small 3 mV rightward shift reported here. In the human cardiac Na channel isoform hH1, mutation of the outermost arginine in IIS4 to histidine caused a similar modest depolarizing shift in the conductance-voltage relationship and no change in the voltage dependence of inactivation (Chen et al, 1996).…”
Section: Role Of Iis4 In Nasupporting
confidence: 62%
“…A charge-neutralizing arginine-to-cysteine substitution at the same position in hSkM1 (R669C) caused only a modest depolarizing shift of the G-V relationship of 5-7 mV (Mitrovic et al, 1998;Groome et al, 1999), similar to the small 3 mV rightward shift reported here. In the human cardiac Na channel isoform hH1, mutation of the outermost arginine in IIS4 to histidine caused a similar modest depolarizing shift in the conductance-voltage relationship and no change in the voltage dependence of inactivation (Chen et al, 1996).…”
Section: Role Of Iis4 In Nasupporting
confidence: 62%
“…Mutation of this positively charged arginine results in the general set of biophysical defects associated with paramyotonia congenita mutants, including slowed whole-cell current inactivation, reduced voltage-dependence of inactivation, enhanced rate of the recovery from inactivation and increased tetrodotoxin (TTX)-sensitive persistent (late) I Na . [7][8][9][10][11][12] These features lead to enhanced Na + entry into the cell causing depolarization of the resting membrane potential and sustained action potential firing which results in hyperexcitability (myotonia) or inexcitability (paralysis). 10,13,14 Current therapies for patients with…”
Section: Introductionmentioning
confidence: 99%
“…Since the position of the S4 gating charge is biased towards the cytosolic side, the outermost charges may contribute to the initial gating charge transfer across the transmembrane electric field upon membrane depolarization. [32][33][34][35] When the outermost charge of a sensor is removed, e.g., R663C in domain-2, the initial activation of this sensor (outward movement) should be less voltage-dependent. If this initial movement of the voltage sensor already weakens the stability of the MrVIA-channel interaction, neutralization of the outermost charged residue is expected to have a strong impact on the kinetics with which MrVIA is repelled from the channel.…”
Section: Discussionmentioning
confidence: 99%